The Islam in Islamic art history: secularism and public discourse - Shaw, Wendy M K (Journal of art historiography, 2012)
Despite the apparent affiliation between religion and art implied in the nomenclature ‘Islamic art history,’ the field has to date relied primarily on secular methodologies. This has limited the potential not only to engage actively in the real-world function of art exhibitions as cultural mediators, but also to use Islamic art to rethink understandings of both the religion and art itself. Instead, this essay argues, the field should engage with a broadened understanding of Islamic discourse as expressed through the interplay of the visual arts with mutually intertwined philosophical, poetic, and religious discourses. In so doing, the discipline of Islamic art history has the potential to enrich the public understanding not only of Islamic art as an aesthetic phenomenon, but also as an expression of aspects of Islam that are often excluded from both ‘Orientalist’ and Islamist approaches to the religion. This essay argues for a more nuanced understanding of ‘Islam’ within Islamic art studies, questioning the binary divide between culture and religion, the exclusions created through ethnocentrism and nationalism, the presentation of Islam as a historical rather than a living faith, and the use of Islam as a trope of heritage rather than as one of a panoply of conceptual frameworks for the modern and contemporary art of cultures that are informed to varying extents by Islam.